The young & prodigious T.S. Spivet [videorecording (DVD)] - Jeunet, Jean-Pierre, 1953-; Catlett, Kyle; Bonham Carter, Helena, 1966-; Rennie, Callum Keith, 1960-; Davis, Judy, 1956-; Larsen, Reif (Anchor Bay Entertainment, 2015)
A ten-year-old cartographer secretly leaves his family's ranch in Montana where he lives with his cowboy father and scientist mother and travels across the country aboard a freight train to receive an award at the Smithsonian Institute.